Pericardial Fat and Right Ventricular Morphology: The Multi-Ethnic Study of Atherosclerosis- Right Ventricle Study (MESA-RV). - David S Wenger; Steven M Kawut; Jingzhong Ding; David A Bluemke; Catherine L Hough; Richard A Kronmal; Joao A Lima; Peter J Leary (PLoS ONE)
Background Pericardial fat has been implicated in the pathogenesis of obesity-related cardiovascular disease. Proposed mechanisms may be relevant in right heart failure, but relationships between pericardial fat and right ventricular (RV) morphology have not been explored. Methods The Multi-Ethnic Study of Atherosclerosis is a prospective cohort that enrolled participants without clinical cardiovascular disease. Pericardial fat was measured using computed tomography and RV parameters using cardiac MRI. Linear regression estimated associations of pericardial fat with RV mass, RV end diastolic volume (RV-EDV), RV end systolic volume (RV-ESV), RV stroke volume (RV-SV), and RV ejection fraction (RV-EF). Limited models adjusted for age, gender, race, height, and study site with and without weight. Fully adjusted models also accounted for socioeconomic parameters and health behaviors. Adjustment for left ventricular morphology, metabolic syndrome, and systemic inflammation was also performed. Results The study sample included 3988 participants with complete assessment of RV morphology, pericardial fat and all covariates. Greater pericardial fat volume was associated with reduced RV mass (-0.3g per 40 cm3 increase in pericardial fat, p<0.001), smaller RV-EDV (-3.7ml per 40 cm3 increase in pericardial fat, p<0.001), smaller RV-ESV (-1.0ml per 40cm3 increase in pericardial fat, p<0.001), and smaller RV-SV (-2.7mL per 40 cm3 increase in pericardial fat, p<0.001) in participants after adjustment for weight. Associations were unchanged when accounting for health behaviors, markers of systemic inflammation, and the metabolic syndrome. Conclusions Greater pericardial fat was associated with reduced RV mass, smaller RV-EDV, smaller RV-ESV, and smaller RV-SV in participants after adjustment for weight. Relationships between pericardial fat and RV morphology could be relevant to diseases of right heart failure.